Instytucja odroczonego warunkowego zwolnienia skazanych w postępowaniu karnym wykonawczym art. 164 § 2 k.k.w. - Myrna, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author of the article examines suspended conditional release in criminal enforcement proceedings Article 1642 of the Criminal Enforcement Code. He discusses the institution in question, presenting its origins, analysing the provisions concerning both the substantive and formal legal rules and basis of such conditional release, as well as considering its usefulness in social reintegration of former prisoners.
Keywords: kodeks karny wykonawczy; zawieszone waunkowe zwolnienie; więzień